2014
DOI: 10.1002/jcc.23777
|View full text |Cite
|
Sign up to set email alerts
|

How does hybrid bridging core modification enhance the nonlinear optical properties in donor‐π‐acceptor configuration? A case study of dinitrophenol derivatives

Abstract: This study spotlights the fundamental insights about the structure and static first hyperpolarizability (β) of a series of 2,4-dinitrophenol derivatives (1-5), which are designed by novel bridging core modifications. The central bridging core modifications show noteworthy effects to modulate the optical and nonlinear optical properties in these derivatives. The derivative systems show significantly large amplitudes of first hyperpolarizability as compared to parent system 1, which are 4, 46, 66, and 90% larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The FF approach has been widely used to calculate the rst hyperpolarizability of numerous chemical systems and has provided very consistent results when compared with the experimental data. 52,53 Herein, we have applied various methods, including B3LYP, HF, range separated hybrid functionals, such as CAM-B3LYP and wb97xd, and long range corrected LC-BLYP at the 6-31G* basis set for calculating the dipole moment and rst hyperpolarizability, and compared them with each other. In general, in the FF approach, a static electric eld (F) is applied and the energy (E) is expressed by the following equation:…”
Section: Computational Methodologymentioning
confidence: 99%
“…The FF approach has been widely used to calculate the rst hyperpolarizability of numerous chemical systems and has provided very consistent results when compared with the experimental data. 52,53 Herein, we have applied various methods, including B3LYP, HF, range separated hybrid functionals, such as CAM-B3LYP and wb97xd, and long range corrected LC-BLYP at the 6-31G* basis set for calculating the dipole moment and rst hyperpolarizability, and compared them with each other. In general, in the FF approach, a static electric eld (F) is applied and the energy (E) is expressed by the following equation:…”
Section: Computational Methodologymentioning
confidence: 99%
“…The theoretically observed values of first‐order hyperpolarizability (β) and second‐order hyperpolarizability (γ) for 2‐napthol azo dyes 1–4 are larger than the values for hyperpolarizability of urea . Moreover, the β and γ values of these dyes were compared with the reported donor‐π‐acceptor dyes . We found that β and γ values of these dyes are competes with the reported donor‐π‐acceptor dyes supplementary information (Table S30).…”
Section: Resultsmentioning
confidence: 83%
“…TPA is a typical third-order NLO absorption phenomenon. To compare the effect of polymerization on the third-order NLO properties, DFT/B3LYP/6-31+G­(d) is utilized to calculate the second static hyperpolarizabilities (γ ijkl ) using Gaussian 09.…”
Section: Theories and Computational Methodsmentioning
confidence: 99%